Monitoring of Plum Pox Virus concentration at different plant heights throughout the year in prunes (Prunus domestica) in Argentina - Marini, Diana Beatriz; Farrando, Roberto Jes; Porcel, Laura Beatriz; Ojeda, Eva Maria; Picca, Cecilia Nelida; Fuentes, C.; Dal Zotto, Angelica; Teich, Ingrid (International Society for Horticultural Science, 2019)
II International Symposium on Plum Pox Virus